Dolikoektasia Serebral Multipel sebagai Faktor Potensial Penyebab Perdarahan Intrakranial dan Intraventrikular Selama Krisis Hipertensi: Laporan Kasus: Laporan Kasus - Basja, Agnes Triana; Fikriyah, Lathifatul (Cermin Dunia Kedokteran, 2026)
Introduction: Dolichoectasia (DE) represents an uncommon vascular anomaly of the brain, characterized by abnormal dilation and elongation of cerebral blood vessels. Its occurrence is relatively rare, with an estimated prevalence ranging from 0.05% to 0.06%. Although predominantly observed within the vertebrobasilar system, cases involving the anterior cerebral circulation have also been documented. Patients with DE are susceptible to intracranial and intraventricular hemorrhage. Case: A 54-year-old male with sudden extremity weakness, hypertensive crisis, and hyperlipidemia. CT imaging showed intracranial hemorrhage in the left thalamic and intraventricular hemorrhage in the posterior horn of the left ventricle with enlargement and tortuosity of the intracerebral artery and vertebrobasilar artery. These imaging findings led to a diagnosis of multiple cerebral dolichoectasia. The patient underwent conservative management with antihypertension and decompression therapy, leading to a gradual alleviation of symptoms. Discussion: Hypertension is considered the major risk factor for intracranial hemorrhage in this patient, while dolichoectasia may represent an associated vascular abnormality that potentially increases vessel wall vulnerability. Structural alterations in dolichoectatic vessels, including disruption of elastic fibers and remodeling of the tunica media, may contribute to reduced vascular integrity under severe hemodynamic stress. The coexistence of hypertensive crisis and multiple dolichoectasia may therefore increase susceptibility to hemorrhagic complications. Conclusion: CT imaging is essential for the diagnosis of dolichoectasia and the detection of associated complications, including intracranial and intraventricular hemorrhage. Early and accurate diagnosis may improve patient outcomes by enabling appropriate therapy.